Analyzing the Impact of Environmental Factors, Employee Social Awareness, and Corporate Social Responsibility on Sustainability Performance - Mohammad Gifari Sono; Tia Nurapriyanti; Acep Fatchuroji; Eva Yuniarti Utami; Roosganda Elizabeth (Eastasouth Institute, 2023)
The purpose of this study is to investigate and analyze how environmental factors, employee social awareness, and corporate social responsibility (CSR) impact the sustainability performance of an organization or company. This study explores the complex interactions between environmental factors, employee social awareness, corporate social responsibility (CSR) practices, and their combined influence on sustainability performance in the manufacturing sector in West Java, Indonesia. In an era marked by increasing concerns about environmental sustainability and corporate responsibility, understanding the dynamics of these factors is critical for organizations seeking to balance economic success with ethical and environmental responsibility. Using a mixed methods research approach, this study combines a quantitative survey of 150 samples with qualitative insights from interviews and analysis of CSR reports from 5 informants. The findings of this study provide a holistic perspective on how these variables collectively shape sustainability performance in manufacturing companies in West Java.